2012
DOI: 10.3892/mmr.2012.1242
|View full text |Cite
|
Sign up to set email alerts
|

The role of p21 3′UTR gene polymorphism in the risk of prostate cancer: A pilot study

Abstract: The cell cycle regulator p21 plays an important role in regulating critical cell activities including cell cycle control, DNA repair and apoptosis. Consequently, it may affect the efficacy of the response to DNA damage and tumor development. The aim of our study was to evaluate the frequencies of the p21 C70T polymorphism, the association between this genetic variant and smoking status, and the serum prostate-specific antigen (PSA) levels and Gleason score in 118 prostate cancer patients and 130 males routinel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…However, the present study found no significant association between this polymorphism and prostate cancer risk (OR=1.06; 95% CI, 0.72-1.58; P>0.05), as was also previously reported in our relatively small pilot study (47). Only one published case-control study evaluated the association of the p21 C70T polymorphic genotypes CT and TT with the risk of advanced prostate carcinoma in a European-American population (OR=2.24; 95% CI, 1.02-4.95) and these genotypes were more strongly associated with more aggressive metastatic disease (androgen-independent disease or fatality from metastatic prostate carcinoma) (48).…”
Section: Non-smokerscontrasting
confidence: 34%
“…However, the present study found no significant association between this polymorphism and prostate cancer risk (OR=1.06; 95% CI, 0.72-1.58; P>0.05), as was also previously reported in our relatively small pilot study (47). Only one published case-control study evaluated the association of the p21 C70T polymorphic genotypes CT and TT with the risk of advanced prostate carcinoma in a European-American population (OR=2.24; 95% CI, 1.02-4.95) and these genotypes were more strongly associated with more aggressive metastatic disease (androgen-independent disease or fatality from metastatic prostate carcinoma) (48).…”
Section: Non-smokerscontrasting
confidence: 34%
“…We failed to find associations with other cell cycle genetic susceptibility alleles which have been associated with risk of prostate cancer. Variants within CDKN1A have been found to be associated with risk of disease by both ourselves and others . We studied both of the variants previously implicated (rs1059234 and rs1801270) and failed to demonstrate an association.…”
Section: Discussionmentioning
confidence: 84%
“…In the current study, we observed no significant association between rs1059234 and rs1801270 polymorphisms of P21 gene and PTC risk. However, the association between these polymorphisms, risk of squamous cell carcinoma, 36 sporadic colorectal cancer, 37 cervical cancer, 34 prostate cancer, 38 uterine leiomyoma, 24 and Gastrointestinal Tract Tumor 39 has been reported previously. We also found no significant association between P21 polymorphisms (rs1059234 and rs1801270) and pathological and clinical characteristics of PTC.…”
Section: Discussionmentioning
confidence: 92%